Hepatic osteodystrophy and fracture risk prediction using FRAX tool in Indian patients with cirrhosis. Issue 5 (12th June 2020) - De, Arka; Ray, Debadrita; Lamoria, Sandeep; Sharma, Vishal; Khurana, Tilak Raj
Abstract : Hepatic osteodystrophy is widely prevalent among Indian patients with cirrhosis and entails a high risk of fractures. Approximately one‐third of patients with cirrhosis need treatment to reduce the risk of osteoporotic fractures. Abstract: Background and Aim: The main clinical relevance of hepatic osteodystrophy is the increased risk of fractures. Dual‐energy X ray absorptiometry (DEXA)‐based assessment of bone mineral density, the current gold standard for diagnosing osteoporosis, is not the sole determinant of fracture risk. Other clinical risk factors also play an important role. This study was carried out to assess the prevalence and risk factors of hepatic osteodystrophy and estimate the entailed fracture risk by using the FRAX tool in a cohort of Indian cirrhotics. Methods: Consecutive patients with cirrhosis ( n = 120) were recruited. Etiologic workup, liver function tests, serum calcium, phosphate, 25(OH)D, HbA1c, and DEXA scan were performed. Hepatic osteodystrophy was defined as a T score of < −1. FRAX scores were calculated using the Indian calculator. Results: The study cohort was predominantly male (86.7%) with a median age of 49 (40–65) years. Alcohol was the most common etiology (80%). All patients had Child‐Turcotte‐Pugh class B (63.3%) or class B (36.7%) cirrhosis. Hepatic osteodystrophy was present in 83.3% patients. On multivariate analysis, smoking (odds ratio [OR]: 3.1 [1.76–4.7], P < 0.001) and serum 25(OH)D (OR: 0.23 [0.09–0.94]; P = 0.03) showed significant association with hepatic osteodystrophy. The 10‐year probability of major osteoporotic fracture and hip fracture was 5.7% (2.1–28.9) and 2.5% (1.4–7.4), respectively. Using a FRAX probability cut‐off of 20% for major osteoporotic fracture and 3% for hip fracture, 30% patients qualified for osteoporosis treatment. Conclusion: Hepatic osteodystrophy is widely prevalent among Indian patients with cirrhosis and entails a high risk of fractures. Approximately one‐third of patients with cirrhosis need treatment to reduce the risk of osteoporotic fractures.